GREEN ROOFS AS AN ESSENTIAL ELEMENT OF MODERN URBAN ENVIRONMENT - Alexander Pregyov; Veselin Rangelov (World Science, 2023)
The need for the realization of green roof spaces has grown significantly in the last few decades, due to increasingly compacted urban spaces, which deprives urbanized territories of green areas. The positive sanitary and hygienic effect, the retention of dust particles and the improvement of the microclimate of roof gardens is a fact. This report presents comparative analyzes with selected european examples in the construction of green roofs. Suitable plant species and their requirements for this type of environment are described. Possibilities for a more tendentious integration of this type of landscaping in Bulgaria are presented.